Molecular characterization of the predominant influenza A(H1N1)pdm09 virus in Mexico, December 2011-February 2012. - Daniela de la Rosa-Zamboni (Public Library of Science (PLoS), 2012)
When the A(H1N1)pdm09 pandemic influenza virus moved into the post-pandemic period, there was a worldwide predominance of the seasonal influenza A(H3N2) and B viruses. However, A(H1N1)pdm09 became the prevailing subtype in the 2011-2012 influenza season in Mexico and most of Central America. During this season, we collected nasopharyngeal swabs of individuals presenting with influenza-like illness at our institution in Mexico City. Samples were tested for seasonal A(H3N2) and B influenza viruses, as well as A(H1N1)pdm09 by real-time reverse transcription-polymerase chain reaction. Of 205 samples tested, 46% were positive to influenza, all of them A(H1N1)pdm09. The clinical characteristics of patients showed a similar pattern to the 2009 pandemic cases. Using next generation sequencing, we obtained whole genome sequences of viruses from 4 different patients, and in 8 additional viruses we performed partial Sanger sequencing of the HA segment. Non-synonymous changes found in the Mexican isolates with respect to the prototype isolate H1N1 (A/California/04/2009) included HA S69T, K163R and N260D unique to 2012 Mexican and North American isolates and located within or adjacent to HA antigenic sites; HA S143G, S185T, A197T and S203T previously reported in viruses from the 2010-2011 season, located within or adjacent to HA antigenic sites; and HA E374K located in a relevant site for membrane fusion. All Mexican isolates had an oseltamivir-sensitive genotype. Phylogenetic analysis with all 8 influenza gene segments showed that 2012 Mexican sequences formed a robust, distinct cluster. In all cases, 2012 Mexican sequences tended to group with 2010-2011 Asian and European sequences, but not with 2009 Mexican sequences, suggesting a possible recent common ancestor between these latter regions and the 2012 Mexican viruses. It remains to be defined if these viral changes represent an important antigenic drift that would enable viral immune evasion and/or affect influenza vaccine effectiveness.